Pengaruh Desain Postur Tubuh Dan Atribut Sebagai Media Ungkap Penggambaran Sifat Karakter Pada Desain Karakter Nine (2009) - Azhari, Irfan; Afif, Riky Taufik (Besaung : Jurnal Seni Desain dan Budaya, 2025)
The characters in the animated film Nine (2009) are one example of an animated film that highlights the depiction of characters based on shape, posture, and attributes as their visual selling point. According to Mars Caroline in her book Animated Character Design, the behavior and traits of a character can be seen based on the body shape and attributes it wears. This study aims to determine the influence of form and attributes as a medium to express the depiction of traits in animated character design. The research method uses descriptive qualitative data by collecting primary data, namely observation and documentation in the film Nine (2009). The secondary data by reading similar research on the topic of character design. This study took three main figures as samples, namely Number One, Number Eight, and Number Nine, as a limitation of the problem to be studied. The data that has been obtained is then analyzed by considering the elements of character design. The results of the study showed that posture and attributes had a significant effect on the depiction of character traits and behaviors. The more complete and distinctive the attributes worn, the easier it is for the character to be recognized both in terms of character and behavior. Meanwhile, posture, especially through body movements and poses, can provide an idea to know the behavior of the character visually. This research is expected to contribute as a reference both in the process of designing animated character designs and as a reference for research.